EVALUASI PELAKSANAAN HOME VISIT DI SMP - Bernardinus Agus Arswimba (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
ABSTRACT Home visit is a responsive service that is urgent, so it needs to be implemented immediately to help students solve problems faced. If home visit is not done well, the problem will have a more complex impact on students. The purpose of the study was to determine the performance of counselors according to or not with the standards and professional counselor evaluation criteria for Comprehensive (Evaluation Model South Carolina) counseling guidance to make decisions or follow-up the programs that have been implemented. The research method used is descriptive evaluation using the Model Evaluation Discrepancy. This model measures the difference between performance standards and real conditions that have been implemented. The instrument of this research is using questionnaires and interviews. The results showed that home visits conducted by counselors at Santa Maria Malang Middle School in the category